EVOLUTION OF CHARACTER IN USMON NOSIR'S DRAMA "ATLAS" - Norboyeva Zarina Yusuf qizi (International Journal of Literature and Language Studies, 2026)
This article examines the skill of creating characters in the drama "Atlas" by Usmon Nosir. The study analyzes the inextricable link between dramatic conflict, dramatic action, and character evolution. The artistic function of the main characters of the work, Orzumand, Atlas, Nozim, and the professor, and their role in the development of the conflict are highlighted. In particular, the development of the image of Orzumand from jealousy and distrust to spiritual maturity, the steadfastness of the image of Atlas, and the function of the image of Nozim in intensifying the conflict are evaluated based on the criteria of drama poetics. As a result of the study, it is substantiated that Usmon Nosir managed to reveal dramatic characters not through the narration of events, but through conflict and spiritual experiences, and character evolution is one of the important poetic factors ensuring the ideological and artistic integrity of the work.